(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of this study is to compare the effectiveness between Mulligan’s mobilization and spencer technique.The study’s 36 patients who met the eligibility requirements were accepted. Before beginning any examinations, each participant in this study completed a written informed consent form. Three groups of frozen shoulder patients were randomly assigned. Mulligan’s mobilization was used in Group A, Spencer technique was used in Group 2, and simply conventional treatment was used in Group 3. The computer-generated list used to divide the patients into the three groups remained consistent throughout the trial. In both groups, the course of treatment lasted four weeks.Shoulder pain is very common problem now a days. Shoulder pain leads to multiple dysfunctions depending upon severity of pain. It decreases the range of motion and leads to functional dependency. Physical therapy is important in the management of shoulder pain including heat therapy, infrared radiations, and manipulation exercises and in some cases traction. This study provided an opportunity to share my personal experience with community. This study was conducted purely in clinical setting of Physiotherapy Department Mayo Hospital, Lahore. The outcome of this study is of great value in treating frozen shoulder which is a great contribution to the health care system of Pakistan. As there are numerous treatment strategies to treat shoulder pain but there is not enough evidence about the efficacy of Spencer technique. Hence this study was done to compare the efficacy of these interventions.NPRS AND SPADI post treatment scores of group A show significant improvement in reducing pain and disability.It was concluded from the results of this study that Mulligan’s mobilization are more effective than Spencer technique for treatment of frozen shoulder. It improves movements and posture of patients.